IMPLEMENTASI DAN DAMPAK E-COURT (ELECTRONICS JUSTICE SYSTEM) TERHADAP ADVOKAT DALAM PROSES PENYELESAIAN PERKARA DI PENGADILAN NEGERI SELONG - Bq., Paridah (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2020)
This thesis aims to determine how the impact on theapplication of the e-court application on advocates in theprocess of solving cases in the Selong district court, as well asto fine out what are the obstacles to the application of the ecourt application. The benefits of this research are expected toprovide knowledge about e-court and the steps in –ecourtoperation with the principle of simple, fast and low cost.Theresearch method used is empirical normative legal researchmethods. The results of this study indicate that the stipulationof perma no.3 of 2018 jo perma no 1 of 2019 concerning theadministration of cases and trials in court electronically showsquite good results and can be applied by all lawyers.